Protective and immunomodulatory effects of the novel probiotic yeast Pichia kudriavzevii isolated from a home-made kefir during infection in human colon epithelial cells: An exploratory study - Angela Maione; Marianna Imparato; Annalisa Buonanno; Marilena Galdiero; Elisabetta de Alteriis; Marco Guida; Emilia Galdiero (Journal of Functional Foods)
In this study we aimed to explore the protective effects of a probiotic yeast Pichia kudriavzevii (Y1) and its cell-free supernatant (CFS-Y1) during infection simulated in vitro using Caco-2 cells. Results showed that both live P. kudriavzevii and CFS-Y1 effectively decreased Salmonella spp. adhesion and invasion, in competition, inhibition and displacement assays, displaying the most potent inhibitory effects when Caco-2 cells were preincubated with Y1/ CFS-Y1 at different concentrations and then bacteria were added for an additional time. Furthermore, the treatment of LPS-induced Caco-2 cells with both Y1 and its CFS-Y1 effectively relieved the oxidative stress and improved the intestinal TJ barrier function. In particular, Y1 and CFS-Y-1 prevented damage to the intestinal epithelial function in LPS-induced Caco-2 cells by upregulating TJ protein expression and reducing ROS accumulation, as well as overproducing anti-inflammatory cytokines. Therefore, the Y1 and its CFS-Y1 possess potential effects on the maintenance of human health and could be considered as a dietary supplementation for food and a promising approach to treat intestinal barrier dysfunction.